DEVELOPMENT OF NON-CASH CIRCULATION AND PAYMENT INFRASTRUCTURE IN THE RUSSIAN FEDERATION - E. Klimova (Вестник университета)
Ensuring the stability and development of conditions for the implementation of non-cash transfers has become one of the main tasks of Russia’s economic policy in order to achieve full integration into global financial relations over the past ten years. There are still many questions and problems that impede the country’s transition to a new level of money transfers between citizens and overcoming mistrust of the population towards electronic instrument of payment. The article examines the main changes in non-cash circulation, and changes in the state of the infrastructure to ensure the availability and continuity of electronic payments in the territory of the Russian Federation.